Harnessing the immune system by targeting immune checkpoints: Providing new hope for Oncotherapy - Yu, Lu; Sun, Minghan; Zhang, Qi; Zhou, Qiao; Wang, Yi (Frontiers in Immunology, 2022)
The advent of immunotherapy revolutionized the cancer field, with the goal of harnessing the host’s immune system to provide long-lasting remission and cures for various cancers. Amongst current immunotherapeutic strategies, immune checkpoint blockade has greatly improved the overall survival rates in certain patient populations. Of note, CTLA-4 and PD-1/PD-L1 are two major non-redundant immune checkpoints implicated in promoting cancer immune evasion, and ultimately lead to relapse. Antibodies or inhibitors targeting these two checkpoints have achieved some encouraging clinical outcomes. Further, beyond the canonical immune checkpoints, more inhibitory checkpoints have been identified. Herein, we will discuss recent updates and progress in immune checkpoint blockade therapies, with a specific focus on summarizing key pre-clinical and clinical results of new immune checkpoint therapies for cancer. Given the crucial roles of immune checkpoint blockade in oncotherapy, drugs targeting checkpoint molecules expressed by both cancer and immune cells are in clinical trials, which will be comprehensively summarized in this review. Taken together, investigating combinatorial therapies targeting immune checkpoints expressed by cancer cells and immune cells will greatly improve immunotherapies that enhance host elimination of tumors.